Mechanical thrombectomy for acute ischemic stroke with occlusion of the M2 segment of the middle cerebral artery: a meta-analysis. (10th November 2017) - Saber, Hamidreza; Narayanan, Sandra; Palla, Mohan; Saver, Jeffrey L; Nogueira, Raul G; Yoo, Albert J; Sheth, Sunil A
Abstract : Background: Endovascular thrombectomy has demonstrated benefit for patients with acute ischemic stroke from proximal large vessel occlusion. However, limited evidence is available from recent randomized trials on the role of thrombectomy for M2 segment occlusions of the middle cerebral artery (MCA). Methods: We conducted a systematic review and meta-analysis to investigate clinical and radiographic outcomes, rates of hemorrhagic complications, and mortality after M2 occlusion thrombectomy using modern devices, and compared these outcomes against patients with M1 occlusions. Recanalization was defined as Thrombolysis in Cerebral Infarction (TICI) 2b/3 or modified TICI 2b/3. Results: A total of 12 studies with 1080 patients with M2 thrombectomy were included in our analysis. Functional independence (modified Rankin Scale 0–2) rate was 59% (95% CI 54% to 64%). Mortality and symptomatic intracranial hemorrhage rates were 16% (95% CI 11% to 23%) and 10% (95% CI 6% to 16%), respectively. Recanalization rates were 81% (95% CI 79% to 84%), and were equally comparable for stent-retriever versus aspiration (OR 1.05; 95% CI 0.91 to 1.21). Successful M2 recanalization was associated with greater rates of favorable outcome (OR 4.22; 95% CI 1.96 to 9.1) compared with poor M2 recanalization (TICI 0–2a). There was no significant difference in recanalization rates for M2 versus M1 thrombectomy (OR 1.05; 95% CI 0.77 to 1.42). Conclusions: This meta-analysis suggests that mechanical thrombectomy for M2 occlusions that can be safely accessed is associated with high functional independence and recanalization rates, but may be associated with an increased risk of hemorrhage.